Sexual function through decades: association with androgens and cardiometabolic features - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2020)
Aim: This study aimed to determine the change in sexual function among Turkish women through decades and to define the association between sexual dysfunction and androgens and cardiometabolic features. Materials and methods: A total of 206 postmenopausal women aged 50-69 years and 210 premenopausal women aged 30-49 years who applied to menopause and gynecology clinics at a university-affiliated education and research hospital were included in this prospective study. Groups were constructed according to decades (i.e., 30-39, 40-49, 50-59, and 60-69 years). Sexual function was assessed between the groups, using the Female Sexual Function Index (FSFI). Cardiometabolic features and androgen levels were also compared between the groups. Results: Sexual function determined at each decade by FSFI scores were 27.18, 23.11, 18.40, and 11.35, respectively (fourth, fifth, sixth, and seventh decade). Desire, arousal, and satisfaction domains tended to be lower in the 40s than in the 30s. As time passes after the 30s, the total FSFI score decreased until the late 60s. Serum total testosterone, androstenedione, and dehydroepiandrostenedione sulfate (DHEAS) levels decreased through the decades. There was no correlation between cardiometabolic features, androgens, and FSFI scores. Conclusion: According to our survey, sexual function decreases starting at the age of 30 and continues to drop until the late 60s among postmenopausal women. There was no association between sexual dysfunction and androgen levels in premenopausal women. The serum DHEAS level was associated with sexual dysfunction only among postmenopausal women. There was no association between sexual dysfunction and cardiometabolic features in either premenopausal or postmenopausal women.
Keywords: Menopause; sexual dysfunction; Female Sexual Function Index; androgens; aging; cardiometabolic features; POSTMENOPAUSAL WOMEN; PREMENOPAUSAL WOMEN; RISK-FACTORS; METABOLIC SYNDROME; UNITED-STATES; DYSFUNCTION; PREVALENCE; MENOPAUSE; TRANSITION; HYPERTENSION